2017
DOI: 10.1155/2017/4896161
|View full text |Cite
|
Sign up to set email alerts
|

Global Attractors of the Extensible Plate Equations with Nonlinear Damping and Memory

Abstract: We prove in this paper the existence of a global attractor for the plate equations of Kirchhoff type with nonlinear damping and memory using the contraction function method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…As for deterministic plate equations, many authors have showed the existence of global attractors (see [1][2][3][4][5][6][7][8][9]). For the stochastic case, the existence of random attractors for plate equations has been investigated in [10,11,12] on bounded domains.…”
Section: Introductionmentioning
confidence: 99%
“…As for deterministic plate equations, many authors have showed the existence of global attractors (see [1][2][3][4][5][6][7][8][9]). For the stochastic case, the existence of random attractors for plate equations has been investigated in [10,11,12] on bounded domains.…”
Section: Introductionmentioning
confidence: 99%
“…Barbosa and Ma [16] investigated the long-time behavior of an extensible plate equation with thermal memory. Yao and Ma [17] proved the existence of a global attractor for the plate equations of Kirchhoff type with nonlinear damping and memory using the contraction function method.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in ( [26]) Yang and Zhong considered the plate equation with nonlinear damping on bounded domain; Khanmamedov investigated existence of global attractors for the plate equation with a localized damping and critical exponent in an unbounded domain in [7,8]; the similar problem was studied by Xiao in [25]. While as µ = 0, the global attractor of Kirchhoff plate equation with memory was obtained in [23,28] and references therein.…”
mentioning
confidence: 99%